Opportunity Costs: Some Definitions and Examples. - Leininger, Wayne E. (The Accounting Review, 1977)
Abstract The goal of this paper is to develop operational definitions for opportunity costs in profit and cost situations. The static inventory problem under risk is suggested as a means of demonstrating these definitions.